Technics and praxis - Ihde, Don, 1934-2024 (Boston studies in the philosophy of science, 1979)
This book examines how the world is known in the context of technological science, particularly through the contemporary use of instrumentation. Instruments embody the scientific search for knowledge, and in doing so, transform human experience. Examinations of subtle effects of technology are explored in areas such as contemporary music, cinema and television. It is the non-neutrality of technology and its capacity to change experience which forms the major theme of the essays included in this book. Technology is shown to be essential ambiguous in both threat and promise through a series of concrete studies. Both the simple technologies, such as the dentist's probe, and the complex technologies, such as the computer, as shown to have certain invariant features. Also included are critical studies of pioneer thinkers concerned with technology like Martin Heidegger, Hans Jonas, and Paul Ricoeur.